Exercise and oxidative stress: p,otential effects of antioxidant dietary strategies in sports - Pingitore, Alessandro; Pereira Lima, Giuseppina Pace [UNESP]; Mastorci, Francesca; Quinones, Alfredo; Iervasi, Giorgio; Vassalle, Cristina (Elsevier B.V., 2015)
Free radicals are produced during aerobic cellular metabolism and have key roles as regulatory mediators in signaling processes. Oxidative stress reflects an imbalance between production of reactive oxygen species and an adequate antioxidant defense. This adverse condition may lead to cellular and tissue damage of components, and is involved in different physiopathological states, including aging, exercise, inflammatory, cardiovascular and neurodegenerative diseases, and cancer. In particular, the relationship between exercise and oxidative stress is extremely complex, depending on the mode, intensity, and duration of exercise. Regular moderate training appears beneficial for oxidative stress and health. Conversely, acute exercise leads to increased oxidative stress, although this same stimulus is necessary to allow an up-regulation in endogenous antioxidant defenses (hormesis). Supporting endogenous defenses with additional oral antioxidant supplementation may represent a suitable noninvasive tool for preventing or reducing oxidative stress during training. However, excess of exogenous antioxidants may have detrimental effects on health and performance. Whole foods, rather than capsules, contain antioxidants in natural ratios and proportions, which may act in synergy to optimize the antioxidant effect. Thus, an adequate intake of vitamins and minerals through a varied and balanced diet remains the best approach to maintain an optimal antioxidant status. Antioxidant supplementation may be warranted in particular conditions, when athletes are exposed to high oxidative stress or fail to meet dietary antioxidant requirements. Aim of this review is to discuss the evidence on the relationship between exercise and oxidative stress, and the potential effects of dietary strategies in athletes. The differences between diet and exogenous supplementation as well as available tools to estimate effectiveness of antioxidant intake are also reported. Finally, we advocate the need to adopt an individualized diet for each athlete performing a specific sport or in a specific period of training, clinically supervised with inclusion of blood analysis and physiological tests, in a comprehensive nutritional assessment. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Diet; Nutrition; Exercise; Oxidative stress; Antioxidants